Molecular Basis of the Extracellular Ligands Mediated Signaling by the Calcium Sensing Receptor - Zhang, Chen; Miller, Cassandra L.; Gorkhali, Rakshya; Zou, Juan; Huang, Kenneth; Brown, Edward M.; Yang, Jenny J. (Frontiers in Physiology, 2016)
Ca2+-sensing receptors (CaSRs) play a central role in regulating extracellular calcium concentration ([Ca2+]o) homeostasis and many (patho)physiological processes in multiple organs. This regulation is orchestrated by a cooperative response to extracellular stimuli such as small changes in Ca2+, Mg2+, amino acids and other ligands. In addition, CaSR is a pleiotropic receptor regulating several intracellular signaling pathways, including calcium mobilization and intracellular calcium oscillation. Nearly 200 mutations and polymorphisms have been found in CaSR in relation to a variety of human disorders associated with abnormal Ca2+ homeostasis. In this review, we summarize efforts directed at identifying binding sites for calcium and amino acids. Both homotropic cooperativity among multiple calcium binding sites and heterotropic cooperativity between calcium and amino acid were revealed using computational modeling, predictions, and site-directed mutagenesis coupled with functional assays. The hinge region of the bilobed Venus flytrap (VFT) domain of CaSR plays a pivotal role in coordinating multiple extracellular stimuli, leading to cooperative responses from the receptor. We further highlight the extensive number of disease-associated mutations that have also been shown to affect CaSR’s cooperative action via several types of mechanisms. These results provide insights into the molecular bases of the structure and functional cooperativity of this receptor and other members of family C of the G protein-coupled receptors (cGPCRs) in health and disease states, and may assist in the prospective development of novel receptor-based therapeutics.